CHINESE FAMILY BUSINESS SUCCESSION FROM THE FAMILY PERPECTIVE - Li Qi, - (2021)
As a long-standing business organization, family businesses occupy an important position in the world economy. In China, only a few family businesses can continue to the second generation, therefore the succession has become a serious challenge for the continued growth of family businesses. And the lack of family perspective is considered to be the key reason that makes the succession research difficult. This research mainly explores the family's influence and the mechanism on family business succession methods and effects, and attempts to control the family's influence to improve the succession of family business. Based on the results of family business succession research and family research, the family system was described from the two dimensions of family structure and family relationship in the quantitative research. In the exploratory research on the relationship between the family structure and the succession methods of family businesses and the succession effect, based on the succession samples of 131 listed family businesses in China, using public data and information, Logit probability model estimation, regression analysis. It is confirmed that the family structure significantly affects the succession of family businesses. At the same time, the choice of different succession methods did not significantly affect the short-term performance of the sample companies. In the validation research of the relationship between the family relationship and the succession effect of family business, based on the sample of 88 Chinese family businesses' inter-generational succession, questionnaire survey data, factor analysis and regression analysis were used. It is confirmed that, while the family relationship directly affects the succession effect, it also mediates the succession effect through the variable of family commitment to business. This reveals the complex mechanism of the family relationship on succession effect in family business. Keywords: family business succession, family structure, family relationship, succession effect